PSIX-14 Impact of needle-free injection device on injection-site tissue damage in beef sub-primals. (7th December 2018) - Maharjan, D; Rodas-González, A; Tanner, A; Kennedy, V; Kirsch, J; Gaspers, J; Negrin-Pereira, N; Fontoura, A; Bauer, M; Swanson, K; Reynolds, L; Stokka, G; et al.
Abstract: To determine the effect of a needle-free injection device (NFID) on tissue damage and beef sub-primal quality, Angus steers were vaccinated and boostered subcutaneously using needle syringe (NS; n = 20) and the NFID (n=22). The primary vaccination occurred at 60 d of age (right side of the neck), and booster at 120 d after first vaccination (left side of the neck); respectively, both with a bovine viral diarrhea vaccine. The vaccination for both injection systems was on the anterior angle of the neck triangle zone. Infrared thermography (320 x 240 pixels) was performed on d 0, 2, 5 and 7 post-vaccination to measure skin temperature and assess skin reaction (SKINR). Steers were backgrounded in pasture, finished in a feedlot and slaughtered, when reaching a final BW of 605 kg, for further carcass visual tissue damage and histopathological evaluation. Visual inspection of the post-vaccination SKINR was performed 120 d after the last vaccination. The IRT measurement, skin temperatures at the injection site were higher in NS-vaccinated steers than NFID-vaccinated steers ( P < 0.02). In both vaccinations occasions, NFID-steers had a greater proportion of SKINR compared to NS-steers (NFID ≥ 83 vs. NS 0%; P < 0.01).On carcasses, "suspected lesions" were identified in the subcutaneous and seam fat ( 2.6 x 3.8 cm size; NFID = 6 and NS = 3). The core samples obtained from NFID and NS samples were confirmed to have 'no vital lesion' from histopathological examinations. Thus, further analysis of the shear force and the collagen content was not performed. In conclusion, the use of NFID technology does not cause tissue damage and can be used to eliminate the risk of broken needles.